Change management and implementation of total productive maintenance: an exploratory study of Malaysian manufacturing companies - Ramayah, T; Jantan, Muhamad; Hassan, Mohd Mustapha (Sekolah Pengurusan, Universiti Utara Malaysia, 2002)
This study examines the effects of change management towards the implementation of productivity and quality improvement programs through the concept of Total Productive Maintenance (TPM), in manufacturing firms in Malaysia. The factors measured are management commitment, training and education, employee empowerment, team culture and company policies and goals for change management. Autonomous maintenance and planned maintenance factors were used to measure TPM. The findings of the study provide empirical evidence that change management factors significantly enhances the extent of TPM implementation